Bayesian estimation of parametric uncertainties, quantification and reduction using optimal design of experiments for CO2 adsorption on amine sorbents. (4th October 2015) - Kalyanaraman, Jayashree; Fan, Yanfang; Labreche, Ying; Lively, Ryan P.; Kawajiri, Yoshiaki; Realff, Matthew J.
Abstract : Highlights: Bayesian estimation and quantification of CO2 adsorption isotherm parameters. Parallel computation in uncertainty propagation and utility function evaluation. Demonstrated optimal experimental design to reduce prediction uncertainty. Integrated UQ framework developed in Python. Abstract: Uncertainty quantification plays a significant role in establishing reliability of mathematical models, while applying to process optimization or technology feasibility studies. Uncertainties, in general, could occur either in mathematical model or in model parameters. In this work, process of CO2 adsorption on amine sorbents, which are loaded in hollow fibers is studied to quantify the impact of uncertainties in the adsorption isotherm parameters on the model prediction. The process design variable that is most closely related to the process economics is the CO2 sorption capacity, whose uncertainty is investigated. We apply Bayesian analysis and determine a utility function surface corresponding to the value of information gained by the respective experimental design point. It is demonstrated that performing an experiment at a condition with a higher utility has a higher reduction of design variable prediction uncertainty compared to choosing a design point at a lower utility.